Civil Society Engagement Strategies for Promoting Good Governance in Nigeria’s Fourth Republic: Comparative Evidence from SERAP and BudgIT - Yusuf Garba Manjo; Kafayat Abidemi Zubair (JURNAL EKONOMI AKUNTANSI MANAJEMEN AGRIBISNIS, 2026)
Since Nigeria transitioned to democratic rule in 1999, persistent challenges of corruption, weak accountability, and limited citizen participation have continued to undermine the consolidation of good governance in the Fourth Republic. In this context, Civil Society Organisations (CSOs) have emerged as critical non-state actors seeking to bridge accountability gaps and enhance transparency within the governance process. This research examines the role of civil society engagement in promoting good governance in Nigeria through a comparative analysis of the strategies employed by the Socio-Economic Rights and Accountability Project (SERAP) and the BudgIT Foundation (BudgIT) during the Tinubu Administration. The primary purpose of the research is to assess how distinct civil society engagement models—judicialised accountability and data-driven transparency—contribute to accountability, transparency, and participatory governance. The research adopts a qualitative research design anchored in a comparative case research approach, relying exclusively on secondary data drawn from organisational reports, court documents, policy briefs, scholarly literature, and credible media sources. Data were analysed using thematic content analysis to identify recurring patterns and comparative insights. The findings reveal that SERAP’s strategic litigation and rights-based advocacy strengthen horizontal accountability by activating judicial oversight, while BudgIT’s civic-technology initiatives enhance social accountability by democratising fiscal information and empowering citizen engagement. However, both models face institutional and enforcement constraints that limit their overall impact. The research concludes that no single civil society strategy is sufficient to secure good governance in Nigeria. This research contributes to civil society and governance scholarship by empirically demonstrating differentiated accountability pathways within Nigeria’s Fourth Republic.